1997
DOI: 10.1111/j.1442-2042.1997.tb00166.x
|View full text |Cite
|
Sign up to set email alerts
|

PCNA and p53 in Urinary Bladder Cancer: Correlation with Histological Findings and Prognosis

Abstract: Background: This study aimed to immunohistochemically examine the expression of proliferating cell nuclear antigens (PCNA) and p53 protein in transitional cell carcinomas (TCC) of the urinary bladder, and to investigate possible correlations of this expression with the tumor grade or stage, tumor recurrence, and prognosis of the disease. Materials and Methods:The immunohistochemical status of the PCNA and p53 proteins were determined on paraffin-embedded sections from 128 patients with TCC of the urinary bladd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
1
10
0
3
Order By: Relevance
“…Literature data on the prognostic value of p53 immunoreactivity are controversial [5, 6, 7]. However, in contrast to previously published data, this is one of the few series in which the prognostic relevance of p53 immunohistochemistry was evaluated in a very homogeneous group of patients.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Literature data on the prognostic value of p53 immunoreactivity are controversial [5, 6, 7]. However, in contrast to previously published data, this is one of the few series in which the prognostic relevance of p53 immunohistochemistry was evaluated in a very homogeneous group of patients.…”
Section: Discussionmentioning
confidence: 49%
“…A number of retrospective studies has shown a correlation between p53 immunoreactivity and tumour grade and stage, which may be of prognostic relevance in superficial bladder cancer. However, the clinical data as to the significance of p53 as a prognostic indicator are controversial [5, 6, 7]. …”
Section: Introductionmentioning
confidence: 99%
“…High levels of p53 protein have been associated with high grade [35], high–stage tumours [36], cell proliferation [12, 13]and poor survival [12]in TCC of the bladder. The role of p53 protein in progression of superficial bladder cancer has been studied recently by different authors [10, 11, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29]with conflicting results: whereas some authors observed that p53 expression studied by immunohistochemistry was an independent prognostic marker for bladder cancer [11, 14, 16, 19, 20, 27, 28], others found that p53 was not of prognostic importance or that it was not independent of other markers [10, 15, 17, 18, 21, 22, 23, 24, 25, 26, 29]. Most of these studies used a small number of superficial bladder cancer patients and they evaluated both Ta and T1 tumours.…”
Section: Discussionmentioning
confidence: 99%
“…p53 overexpression has been proven to be related to high stage [10, 11], rapid proliferation [12, 13]and poor survival [11]. Nevertheless, controversial results on the role of p53 in tumour progression of superficial bladder neoplasms have been reported in the literature [10, 11, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29]. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a decreased p21/WAF1 expression leads to a suppression of the G1-S checkpoint with a decreased time for DNA repair and increases in mutations during DNA replication [9][10][11]. Thus, p21/WAF1 expression may reflect the functional status of p53 [12]. Because p21/WAF1 is induced by p53, a lack of p21/WAF1 expression may help to detect those patients who do not develop tumor progression or recurrence despite a p53 mutation.…”
Section: Introductionmentioning
confidence: 99%